PC-SAFT equation: A predictive tool to determine experimental conditions for polymer blend demixing - Martini, Raquel Evangelina (2009)
The perturbed-chain statistical associating fluid theory equation of state (PC-SAFT) was applied to predict the phase behavior of polymer solutions in order to determine the pressure - temperature region for the high molecular weight polymer blend separation by using n-alkanes at high pressure and high temperature. The polymer blends selected were physical blends of polyethylene (PE)/polystyrene (PS), and polypropylene (PP)/PS. The miscibility and immiscibility region of each polymer in different alkanes (n-pentane, n-hexane, and n-heptane) was studied and from this analysis, the experimental conditions of the polymer blend demixing were predetermined. The results obtained were validated with experimental data indicating that the PC-SAFT equation is a good tool to predict experimental conditions for the processing windows of polymer blend separation.